Modified sucrose, starch, and ATP levels in two alloplasmic male-sterile lines of B. napus - Teixeira, Rita Teresa (Journal of experimental botany, 2005)
Alloplasmic lines of Brassica napus with rearranged Arabidopsis thaliana mitochondrial DNA are male sterile and vegetatively altered compared with B. napus cv. Hanna. The CMS lines contain pure nuclear and plastid genomes from B. napus. Cross-sections of leaves revealed elevated starch accumulation and a higher number of chloroplasts per cell area in CMS plants compared with B. napus. The increase in chloroplast density was found to be the result of the smaller mesophyll cells. Sucrose concentration in the leaves of the CMS lines was reduced both in green leaves as well as in leaves from 2 d-etiolated plants. Flower meristem, flower buds, and leaves from green and 2 d-etiolated plants were analysed for ATP and ADP contents. All CMS plant tissues, except for green leaves, possessed lower ATP levels than B. napus. The results indicate that the reduced availability of energy, i.e. ATP and sucrose in the CMS plants, limits plant growth. This is supported by the reduced levels of two D-type cyclin transcripts and the reduced capacity of the CMS plants to recover after etiolation